2019
DOI: 10.1007/s00421-019-04285-5
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged cooling with phase change material enhances recovery and does not affect the subsequent repeated bout effect following exercise

Abstract: Prolonged cooling with phase change material enhances recovery and does not affect the subsequent repeated bout effect following exercise. European Journal of Applied Physiology, 120 (2). pp. 413-423.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
12
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 62 publications
2
12
1
1
Order By: Relevance
“…A central effect from local 15 • C PCM cooling was since confirmed by the reduction in core temperature and increase in heart rate variability evident during PCM treatment in individuals at rest (Kwiecien et al, 2019). These findings suggested that prolonged PCM cooling delivered a systemic, and not just a local effect; and might explain, in part, the accelerated recovery evident from PCM cooling following eccentric exercise (Kwiecien et al, 2020a), soccer match play (Clifford et al, 2018;Brownstein et al, 2019) and baseball pitching (Mullaney et al, 2020). However, the central effect occurring from PCM cooling remains to be directly elucidated in individuals following exercise.…”
Section: Future Directionsmentioning
confidence: 84%
See 4 more Smart Citations
“…A central effect from local 15 • C PCM cooling was since confirmed by the reduction in core temperature and increase in heart rate variability evident during PCM treatment in individuals at rest (Kwiecien et al, 2019). These findings suggested that prolonged PCM cooling delivered a systemic, and not just a local effect; and might explain, in part, the accelerated recovery evident from PCM cooling following eccentric exercise (Kwiecien et al, 2020a), soccer match play (Clifford et al, 2018;Brownstein et al, 2019) and baseball pitching (Mullaney et al, 2020). However, the central effect occurring from PCM cooling remains to be directly elucidated in individuals following exercise.…”
Section: Future Directionsmentioning
confidence: 84%
“…Recent studies examining the effects of prolonged 15 • C PCM cooling on indices of recovery in untrained (Kwiecien et al, 2018) and trained (Kwiecien et al, 2020a) individuals found that 6 h of PCM cooling not only accelerated recovery of soreness, but also accelerated recovery of strength loss on the days after isolated eccentric quadriceps exercise (Table 1). Importantly, the protection provided by the PCM cooling after an initial bout of eccentric exercise did not interfere with the repeated bout effect, whereby an initial bout confers an adaptive protective effect for a subsequent bout of damaging exercise (Kwiecien et al, 2020a). Similarly, 3 h of 15 • C PCM cooling has also been shown to accelerate recovery of quadriceps strength following soccer match play (Clifford et al, 2018;Brownstein et al, 2019; Table 1) and shoulder internal rotation strength and grip strength following baseball pitching (Mullaney et al, 2020; Table 1).…”
Section: Evidencementioning
confidence: 99%
See 3 more Smart Citations